Isolation of a genomic clone partially encoding human hypoxanthine phosphoribosyltransferase. - Douglas J. Jolly; A C Esty; Hans‐Ulrich Bernard; Theodore Friedmann (1982)
Mouse cells deficient in the enzyme hypoxanthine phosphoribosyltransferase (HPRT; EC 2.4.2.8) have been transfected with total human DNA, and cells producing human enzyme were isolated by growth in selective medium. DNA from several such cell lines has been used to generate secondary transfectants that make human HPRT. Blots of the DNA of these secondary cells have been hybridized with total human DNA probes or with cloned human Alu sequences, and one of several common bands has been cloned in pBR322. Colonies of transformed Escherichia coli containing human sequences were detected by their homology with human DNA, and subclones of resulting recombinant plasmids were prepared. Two subclones free of Alu sequences were found to contain human sequences that hybridized to human X chromosome DNA. One of these, pBR1.5, also hybridized to a single RNA band on gel blots of human and secondary transfectant cytoplasmic poly(A)+RNA but not to RNA from the parent mouse cell line. These results indicate that these clones represent human HPRT gene fragments. This has been confirmed by using pBR1.5 as a probe to isolate an authentic and expressible human HPRT cDNA clone from a library prepared by H. Okayama and P. Berg.